Productive and physiological responses of feeder cattle supplemented with Yucca schidigera extract during feedlot receiving - De Sousa, Osvaldo A. [UNESP]; Cooke, Reinaldo F. [UNESP]; Brandão, Alice P.; Schubach, Kelsey M.; Schumaher, Thiago F. [UNESP]; Bohnert, David W.; Marques, Rodrigo S. (Oxford University Press (OUP), 2019)
This experiment evaluated the effects of supplementing a saponin-containing feed ingredient, manufactured from purified extract of Yucca schidigera [Micro-Aid (MA); DPI Global; Porterville, CA], on performance, health, and physiological responses of receiving cattle. A total of 105 recently weaned Angus x Hereford calves (75 steers and 30 heifers), originating from eight cow-calf operations, were obtained from an auction facility on day-2 and road transported (800 km; 12 h) to the experimental facility. Immediately after arrival on day-1, shrunk BW was recorded and calves were grouped with free-choice access to grass hay, mineral supplement, and water. On day 0, calves were ranked by sex, source, and shrunk BW, and allocated to one of 21 pens (5 calves/pen; being one or two heifers within each pen). Pens were assigned to receive a total mixed ration (TMR) and one of three treatments (as-fed basis): (1) 1 g/calf daily of MA (M1; n = 7), (2) 2 g/calf daily of MA (M2; n = 7), or (3) no MA supplementation (CON; n = 7). Calves received the TMR to yield 15% (as-fed basis) orts, and treatments were top-dressed from days 0 to 59. Calves were assessed for bovine respiratory disease (BRD) signs and TMR intake was recorded for each pen daily. Calves were vaccinated against BRD pathogens on days 0 and 21. Final shrunk BW was recorded on day 60, and blood samples were collected on days 0, 2, 6, 10, 14, 21, 28, 34, 45, and 59. ADG was greater (P = 0.03) in M2 vs. M1 and CON (1.53, 1.42, and 1.42 kg/day, respectively), and similar (P = 0.95) between M1 and CON calves. No treatment effects were detected for TMR intake (P = 0.52), whereas feed efficiency was greater (P ≤ 0.05) in M2 vs. M1 and CON calves (213, 200, and 204 g/kg, respectively) and similar (P = 0.40) between M1 and CON calves. No treatment effects were detected (P = 0.39) for diagnosis of BRD signs. The number of antimicrobial treatments required upon BRD diagnosis was greater (P ≤ 0.01) in CON vs. M1 and M2 (1.40, 1.05, and 1.10 treatments, respectively), and similar (P = 0.60) between M1 and M2 calves. No other treatment effects were detected (P ≥ 0.23), including circulating concentrations of hormones and metabolites, serum antibody titers to BRD pathogens, and mRNA expression of innate immunity genes in whole blood. Collectively, results from this experiment suggest that MA supplementation at 2 g/animal daily enhances performance and response to BRD treatment in high-risk cattle during feedlot receiving.
Keywords: innate immunity; nutrition; performance; receiving cattle; respiratory disease; saponins